Representation of Juvenile Delinquency Factors in the Movie "Dua Garis Biru" - Putr, Sekar Amalia; Dwihantoro, Prihatin (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
Juvenile delinquency is one of the problems in Indonesia that must receive immediate attention, because the quality of future human resources is in the hands of today's youth. With the sophistication of technology, it should be easier for teenagers to express and learn. Like now, a movie can also be an educational land for its audience. The purpose of this study is to analyze the factors that influence juvenile delinquency in the film Dua Garis Biru. This research uses descriptive qualitative method with content analysis. The results of this study are found two outline factors, namely external and internal factors that represent juvenile delinquency factors. In this study, the analysis method used is the semiotic analysis of Charles Sanders Pierce.